Individual differences in behaviour explain variation in survival: a meta‐analysis. (6th December 2019) - Moiron, Maria; Laskowski, Kate L.; Niemelä, Petri T.
Abstract: Research focusing on among‐individual differences in behaviour ('animal personality') has been blooming for over a decade. Central theories explaining the maintenance of such behavioural variation posits that individuals expressing greater "risky" behaviours should suffer higher mortality. Here, for the first time, we synthesize the existing empirical evidence for this key prediction. Our results did not support this prediction as there was no directional relationship between riskier behaviour and greater mortality; however there was a significant absolute relationship between behaviour and survival. In total, behaviour explained a significant, but small, portion (5.8%) of the variance in survival. We also found that risky (vs. "shy") behavioural types live significantly longer in the wild, but not in the laboratory. This suggests that individuals expressing risky behaviours might be of overall higher quality but the lack of predation pressure and resource restrictions mask this effect in laboratory environments. Our work demonstrates that individual differences in behaviour explain important differences in survival but not in the direction predicted by theory. Importantly, this suggests that models predicting behaviour to be a mediator of reproduction‐survival trade‐offs may need revision and/or empiricists may need to reconsider their proxies of risky behaviours when testing such theory. Abstract : Individual variation in behaviour is predicted to be related to differences in individual fitness components such as survival and longevity. Using meta‐analytic techniques, we were able to show that there is indeed a significant relationship between behaviour and survival, with behavioural variation explaining about 6% of the variance in survival. However, this relationship was not in the direction predicted by the key models, implying that current theoretical predictions are not capturing the whole complexity of the phenomenon.